Analisis Strategi Pengembangan Agribisnis Semangka (Citrullus lanatus) Pada CV Tani Makmur Di Kabupaten Jombang - Serli Febrina Wahidiyanti (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
Fruits are a source of vitamins and minerals needed by the body. Apart from being a source of vitamins and minterals, watermelon is one type of fruits that have a high economic value. One company that seizes the watermelon business opportunity is CV Tani Makmur. To maintain the business of watermelon fruit, CV Tani Makmur party needs to do a strategy for the company to grow and avoid the loss. The purpose of this research is (1) An analize the development strategi of watermelon agribusiness, (2) Identify development strategi of internal and external area. This research was conducted from February to June 2017. The results of internal environmental analysis with IFE matrix shows that the business of watermelon CV Tani Makmur has a total score of 3.1234. This value is above the average value of 2.5 indicating that the development of the watermelon business CV Tani Makmur is above average, ie the company is able to utilize its strength quite well. In addition, the company can minimize its weaknesses quite well. While the results of external environmental analysis with the EFE matrix shows that the business of watermelon CV Tani Makmur has a total score of 2.3079. This value is below the average score of 2.5 indicating that in the business development of watermelon fruit, CV Tani Makmur less respond to opportunities that exist. In addition, firms are less able to avoid threats to the watermelon business. Companies can be managed with grow and build strategies. The result of the strategy with the SWOT matrix resulted in seven alternative strategies. The QSP matrix resulted in the priority of the alternative strategy in the business strategy of watermelon fruit of CV Tani Makmur with the highest STAS (Sum Total Attractivity) score is to develop the human resources performance to increase the production and the broader target market with STAS of 5.4266. This strategy is a strategy of utilizing the company's strength to overcome the weakness of the watermelon business of CV Tani Makmur.